Effect of 3 Weeks Use of Compression Garments on Stride and Impact Shock during a Fatiguing Run - Lucas-Cuevas, A. G.; Priego-Quesada, J. I.; Aparicio, I.; Giménez, J. V.; Llana-Belloch, S.; Pérez-Soriano, P. (International Journal of Sports Medicine, 2015)
Excessive and prolonged exposure to impact acceleration during running is associated with increased injury rate. Acute use of compressive garments has been speculated to improve attenuation. However, it is unknown how longer interventions of compressive garments influence attenuation in running. 40 runners trained with compressive and placebo stockings for 3 weeks. Perception of comfort, stride parameters (rate, length) and impact acceleration (head and tibial peak acceleration, magnitude, acceleration rate and attenuation) were measured every 5 min during a fatigue run (30 min at 80% of the individual’s maximal aerobic speed). Compressive stockings reduced tibial peak acceleration and magnitude compared to placebo stockings at every minute (p<0.05) except for the initial measurement (p>0.05). Moreover, compressive stockings led to a lower rate of increase in tibial peak acceleration (14%, p<0.005) and magnitude (16%, p<0.001) as a result of the development of fatigue compared to placebo stockings (24% and 26% increase, p=0.014 and p=0.003, respectively). Similar perception of comfort was reported for both garments. Training with compressive stockings for 3 weeks reduced impact acceleration and the rate of increase in acceleration compared to placebo stockings. These findings suggest that compressive stockings may play a protective role by reducing impact accelerations during running.
Keywords: impact acceleration; graduated compressive stockings; comfort; exertion; shock attenuation